1989
DOI: 10.1021/ac00180a005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antimycin A by reversed-phase liquid chromatography/nuclear magnetic resonance spectrometry

Abstract: A mixture of closely related streptomyces fermentation products, antimycin A, is separated, and the components are identified by using reversed-phase high-performance liquid chromatography with directly linked 400-MHz proton nuclear magnetic resonance detection. Analyses of mixtures of three amino acids, alanine, glycine, and valine, are used to determine optimal measurement conditions. Sensitivity increases of as much as a factor of 3 are achieved, at the expense of some loss in chromatographic resolution, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Ha et al [27] analyzed antimycin A, a mixture of closely related streptomyces fermentation products with antibiotic effects. Due to the unstability of these compounds the on-line detection is a great advantage prior to conventional analysis.…”
Section: Pharmaceutical and Clinical Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Ha et al [27] analyzed antimycin A, a mixture of closely related streptomyces fermentation products with antibiotic effects. Due to the unstability of these compounds the on-line detection is a great advantage prior to conventional analysis.…”
Section: Pharmaceutical and Clinical Chemistrymentioning
confidence: 99%
“…Mixtures of peptides were separated and determined in a short time by Spraul [13]. Ha et al [27] analyzed mixtures of three amino acids. Laude et al [10] as well as Laude and Wilkins [38] reported on the separation of some test mixtures (e.g.…”
Section: Other Applicationsmentioning
confidence: 99%